Studi Deskriptif Persepsi Siswa pada Guru Bimbingan dan Konseling dalam Pelaksanaan Layanan Konseling Individual - Rachmadhani, Dian Putri (Universitas Ahmad Dahlan, 2016)
This study aimed to describe the students perception of guidance and counseling teachers in the implementation of individual counseling services. This research is descriptive quantitative with data collection instruments in the form of a questionnaire. The research subjects was 36 students of grade IX SMP Negeri 2 Kebumen taken through purposive sampling technique. The perception of students towards guidance and counseling teachers in the implementation of individual counseling services were analyzed using a simple calculation with a grouping of three criteria: good, average, and poor. The results showed that students perception of guidance and counseling teachers in the implementation of the services of individual counseling class IX SMP Negeri 2 Kebumen as many as 21 (58%) are in good category, 53 (42%) are in the average category, and 0 (0%) in the poor category. The results of this study can be used as a feedback and self-evaluation materials for guidance and counseling teachers in developing the quality of individual counseling services in schools.